Study on Stress Concentration Factor (SCF) of Gap and Overlap Tubular K-Joint - Md Shamir, Nurul Izzati (Universiti Teknologi PETRONAS, 2019)
Most international codes and specifications require a minimum distance between two adjacent welds avoid adverse effect on the mechanical performance of the welded joint. However, there are overlapping weld that is commonly practiced in the current industries. This study will be mainly concern on stress concentration factor performance between simple gap weld and overlapping weld.